DESIGN AND CONSTRUCTION OF AN INTERNET OF THINGS-BASED AUTOMATIC IRRIGATION SYSTEM FOR DRY LAND - Ramli, Muhamad Hidayat; Ginting, Almido H.; Pollo, Don E. D. G. (Teknik Elektro Universitas Siliwangi, 2025)
This research aims to design and develop an automatic irrigation system for dry land based on the Internet of Things (IoT) to address limited water availability and improve irrigation efficiency. The system utilizes three ESP8266 microcontrollers—one as the master and two as slave nodes. The slave nodes are responsible for reading soil moisture levels using YL-69 sensors, while the master receives data from both nodes, controls the water pump based on water level data from an ultrasonic sensor, and sends commands to solenoid valves via the slave nodes. The system is connected to the Blynk application for real-time monitoring and control and also displays moisture data on an LCD. Test results show that the system functions as intended, with adequate sensor accuracy and the ability to regulate irrigation automatically based on soil moisture thresholds of 70% and 80%. This system is expected to serve as an efficient solution for sustainable dry land management.